ANALISIS PENGARUH BIAYA PRODUKSI DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH PADA PERUSAHAAN SUBSEKTOR SUPERMARKET DAN MINIMARKET - Ani Hidayati; Syifah Fauziah Nur Ainy; Rini Wahyuningroem (Jurnal Aplikasi Perpajakan, 2026)
This study aims to examine and analyze the impact of production costs and operating costs on the net profit of supermarket and minimarket sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative method with a descriptive approach was employed. The study utilized secondary data—specifically, the annual financial statements of supermarket and minimarket sub-sector companies—obtained from the Indonesia Stock Exchange for the 2020–2024 period. Purposive sampling was used as the sampling technique. Data analysis techniques included descriptive statistical analysis, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation tests), multiple linear regression analysis, hypothesis testing, and the coefficient of determination test. The results indicate that production costs have a significant partial effect on net profit, whereas operating costs do not have a significant partial effect on net profit. However, production costs and operating costs simultaneously exert a significant influence on the net profit of supermarket and minimarket sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period.